Microstructural and optical properties of SnO2-ZnSnO3 ceramics - YUMAK YAHŞİ, AYŞE (ELSEVIER SCI LTD, 2016)
This work deals with some physical investigation on SnO2-ZnSnO3 ceramics grown on glass substrates at different temperatures (450 degrees C and 500 degrees C). Structural and optical properties were investigated using X-Ray diffraction (XRD), Raman, infrared (IR) absorption (FTIR), UV-visible spectroscopy and Photoluminescence (PL) techniques. XRD results revealed the existence of a mixture of SnO2/ZnSnO3 phases at different annealing temperatures. Structural analysis showed that both phases are polycrystalline. On the other hand, the optical constants (refractive index, extinction coefficient and the dielectric constants) have been obtained by the transmittance and the reflectance data. The optical band gap energy changed from 3.85 eV to 3.68 eV as substrate temperature increased from 450 degrees C to 500 degrees C. Raman, FTIR modes and PL reinforced this finding regarding the existence of biphasic (SnO2 and ZnSnO3) which is detected also by X-Ray diffraction analysis. Finally, the Lattice Compatibility Theory was evoked for explaining the unexpected incorporation of zinc ions in a rhombohedral structure within SnO3 trigonal lattice, rather than the occupation of SnO2 available free loci. All the results have been discussed in terms of annealing temperature. (C) 2016 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Crystal growth; X-ray diffraction; Crystal structure; ZNO THIN-FILMS; COMPATIBILITY THEORY LCT; SUBSTRATE-TEMPERATURE; GAS SENSORS; CONSTANTS; PHOTOLUMINESCENCE; SNO2; PATTERNS; NANORODS; TERMS